1996
DOI: 10.3758/bf03210752
|View full text |Cite
|
Sign up to set email alerts
|

On the continuity of thought and the representation of knowledge: Electrophysiological and behavioral time-course measures reveal levels of structure in semantic memory

Abstract: Time-coursestudies of semantic verification are reviewed, discussed, and reinterpreted with the aim of drawing general theoretical conclusions about semantic memory structure. These reaction time, speed-accuracy tradeoff, speed-accuracy decomposition, and event-related (brain) potential (ERP) studies suggest that semantic memory is structured on at least three levels. In particular, specific models of the intermediate (macrostructural) level are discussed and compared. ERP investigations of this level sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
4
20
0
Order By: Relevance
“…This result agrees with several previous estimates of the onset of semantic processing derived from scalp and intracranial ERP techniques (e.g., 150-300 msec from ERP, 230 msec in the left inferior frontal region) (10,45). Others have suggested that cognitive processing during naming occurs in the lateral posterior temporal lobe at 700-1,200 msec, as assessed by change of spectral density of the ECoG (46).…”
Section: Discussionsupporting
confidence: 92%
“…This result agrees with several previous estimates of the onset of semantic processing derived from scalp and intracranial ERP techniques (e.g., 150-300 msec from ERP, 230 msec in the left inferior frontal region) (10,45). Others have suggested that cognitive processing during naming occurs in the lateral posterior temporal lobe at 700-1,200 msec, as assessed by change of spectral density of the ECoG (46).…”
Section: Discussionsupporting
confidence: 92%
“…It has therefore proven difficult to draw unequivocal conclusions from such studies. How can we be sure that the category-based effects arise because individuals tap into existing structured representations and not because individuals create structure as needed by the categorization task itself (for review, see Kounios, 1996)?…”
Section: Discussionmentioning
confidence: 99%
“…Both groups found that a final word that was not a category member generated more N400 activity than did a category member. Category effects on the N400 have also been observed during the performance of sentence verification tasks (in which individuals are asked to judge the truth of statements of the form "An X is a Y "-for example, "A robin is a bird") (e.g., Fischler, Bloom, Childers, Roucos, & Perry, 1983;Kounios, 1996;Kounios & Holcomb, 1992). In these tasks, an enlarged N400 response is observed to the final word of false statements such as "A carrot is a fruit."…”
Section: The N400 and Long-term Memorymentioning
confidence: 94%
“…Specifically, N400 is typically oflarger amplitude to words (or pictures) that do not fit their semantic context (e.g., "He put cream and sugar in his dog/coffee," where dog elicits a larger N400 than does coffees. Although a definitive theory ofthe N400 does not yet exist, a number of researchers have argued that this component reflects a mechanism that attempts to integrate a piece of information into its semantic context (e.g., Kounios, 1996;Osterhout & Holcomb, I995)-hence, the larger amplitude in response to a word such as dog that does not fit well. Frenck-Mestre et al (1997) reasoned that if semantic satiation were truly semantic, satiation should diminish the magnitude of the N400 effect (defined as the difference in N400 amplitude to words that fit and do not fit their context).…”
Section: Recent Studiesmentioning
confidence: 99%
“…Frenck-Mestre et al (1997) focused on the N400 component, a negative deflection in the ERP waveform that typically peaks approximately 400 msec after stimulus onset (Kutas & Hillyard, 1980). The N400 component, likely a complex of related subcomponents (see e.g., Holcomb, Kounios, Anderson, & West, 1999;Kounios, 1996;Kounios & Holcomb, 1994), was of particular interest to these investigators, because it has been shown to be sensitive to semantic factors in a variety of tasks (for reviews, see Kounios, 1996;Kutas & van Petten, 1994;Osterhout & Holcomb, 1995). Specifically, N400 is typically oflarger amplitude to words (or pictures) that do not fit their semantic context (e.g., "He put cream and sugar in his dog/coffee," where dog elicits a larger N400 than does coffees.…”
Section: Recent Studiesmentioning
confidence: 99%